2006
DOI: 10.1038/nn1697
|View full text |Cite
|
Sign up to set email alerts
|

Eph receptors are negatively controlled by protein tyrosine phosphatase receptor type O

Abstract: Eph receptors are activated by the autophosphorylation of tyrosine residues upon the binding of their ligands, the ephrins; however, the protein tyrosine phosphatases (PTPs) responsible for the negative regulation of Eph receptors have not been elucidated. Here, we identified protein tyrosine phosphatase receptor type O (Ptpro) as a specific PTP that efficiently dephosphorylates both EphA and EphB receptors as substrates. Biochemical analyses revealed that Ptpro dephosphorylates a phosphotyrosine residue conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 47 publications
6
87
1
Order By: Relevance
“…Analyses of double or triple mutant mice should thus reveal the physiological roles of R3 RPTPs. We previously reported that chick Ptprj cannot dephosphorylate Eph receptors (6). This difference may be attributable to a species difference: the amino acid sequences of the ICR of mouse Ptprj and chick Ptprj have only 78% identity, whereas those of Ptpro have 93% identity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Analyses of double or triple mutant mice should thus reveal the physiological roles of R3 RPTPs. We previously reported that chick Ptprj cannot dephosphorylate Eph receptors (6). This difference may be attributable to a species difference: the amino acid sequences of the ICR of mouse Ptprj and chick Ptprj have only 78% identity, whereas those of Ptpro have 93% identity.…”
Section: Discussionmentioning
confidence: 98%
“…Previously we identified substrates for Ptpro (with a single PTP domain) (6) and Ptprz (with tandem PTP domains) (18,19) by using a two-hybrid system with substrate-trapping RPTP mutants. In this study, we expanded the screening to include almost the entire RPTK family to find substrates for the R3 RPTP subfamily by using mammalian cDNA clones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(i) Using EphA and -B receptors as substrate, GLEPP1 plays a role in axonal guidance (25,26). (ii) GLEPP/PTPRO was characterized as a tumor suppressor gene, with CpG island promoter hypermethylation and reduced expression seen in primary tumors and tumor cell lines (27)(28)(29).…”
mentioning
confidence: 99%